Ein Zwischen Blick auf die Sammlung : Die Graphische Abteilung - Zwischen Raum 96-99. - Rogger, André (Luzern : Kunstmuseum Luzern, 1997)
Schmid, Augustin ; Marzohl, Johann Baptist ; Schwegler, Jakob ; Altishofen, Ignaz Pfyffer von ; Triner, Heinrich ; Zelger, Josef ; Schiffmann, Jost ; Zünd, Robert ; Schwegler, Xaver ; Rhyn, Jost Meyer-am ; Pfyffer, Niklaus ; D.J., Jost Muheim
biografie
Ein Zwischen Blick auf die Sammlung : Die Graphische Abteilung - Zwischen Raum 96-99, Kunstmuseum Luzern, 28. Juni bis 10. August 1997
Duits
boek